Tumour-stromal interactions: Reciprocal regulation of extracellular matrix proteins and ovarian steroid activity in the mammary gland - Haslam, Sandra Z (BioMed Central, 2001)
Despite the critical importance of ovarian steroids in the treatment of breast cancer, little is known about the acquisition or loss of estrogen and progesterone responsiveness in either the normal or neoplastic mammary gland. This review focuses on the interactions among mammary stroma-derived extracellular matrix (ECM) proteins, integrins and ovarian hormone-dependent proliferation in normal and neoplastic mammary cells both in vivo and in vitro. In vitro studies show that fibronectin is required for progesterone-induced proliferation of normal mammary epithelial cells and that specific ECM proteins also regulate interactions between growth factors and ovarian hormones. Studies with human breast cancer cell lines have shown that laminin inhibits estrogen-induced proliferation and estrogen-response-element-mediated transcription in vitro and also inhibits estrogen-induced proliferation in vivo. Reciprocally, ovarian steroids regulate the expression of ECM proteins and their cellular receptors, integrins, during mammary gland development in vivo. The fibronectin-specific integrin, α(5)β(1) is regulated by ovarian steroids and its expression is positively correlated with developmental stages of peak proliferation. These studies suggest that the coordinated regulation of ovarian hormone responsiveness and ECM/integrin expression may be critical to normal mammary gland development and breast cancer growth and progression.